2008
DOI: 10.1002/jbm.a.32235
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth metals used in biodegradable magnesium‐based stents do not interfere with proliferation of smooth muscle cells but do induce the upregulation of inflammatory genes

Abstract: Rare earth metals are added to corrodible magnesium-based alloys in low amounts (up to 10%) to improve their mechanical properties and to decrease the degradation rate. Cerium (Ce), neodymium (Nd), yttrium (Y), and ytterbium (Yb) are already used for degradable cardiovascular stents. Little is known about the biocompatibility of rare earth metals released during the degradation process of the implant. Therefore the biocompatibility of rare earth metals was assessed with regard to metabolic activity of human va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…41 These alloying elements are known to have adverse effects and potential longterm risks, [42][43][44][45] although some studies have reported good biocompatibility. 46,47 Allergic hypersensitivity, reduction of hemoglobin oxygen affinity, and fatty liver are some potential adverse effects of these elements at toxic doses. 43,45 Chelated REE are easily excreted in the urine, and mortality studies have revealed that REE are not highly toxic.…”
Section: Discussionmentioning
confidence: 99%
“…41 These alloying elements are known to have adverse effects and potential longterm risks, [42][43][44][45] although some studies have reported good biocompatibility. 46,47 Allergic hypersensitivity, reduction of hemoglobin oxygen affinity, and fatty liver are some potential adverse effects of these elements at toxic doses. 43,45 Chelated REE are easily excreted in the urine, and mortality studies have revealed that REE are not highly toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Feyerabend et al found that aluminium and lithium exert toxic effects on perivascular cells only at concentrations above 1000 micromole [90]. Except for gadolinium, rare earth elements are only toxic at high concentrations, although calcium antagonistic effects could be shown, which in principle could affect many biochemical reactions, particularly muscle and heart muscle contractions as well as cardiac conduction [110]. Many RE elements have even been said to show some anti-carcinogenic properties [39].…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Similar biocompatibility concerns exist for alloys containing RE, which although studied in vitro [30][31][32][33] and in vivo 34,35 , also suffer from a similar lack of knowledge of their long term effects when implanted. 30,36 This creates the potential that the significant amount of work that has been and will be performed using alloys containing Al/RE may, in the end, go unused if the materials cannot be proven to be non-toxic. One immediate knowledge gap in the literature that should be addressed with some urgency) is the recommended daily dosage limits for RE elements (i.e.…”
Section: ) the Requirement To Alloy Mg: Strength Versus Toxicitymentioning
confidence: 99%